Perlindungan Hukum Hak Asasi Manusia dalam memperoleh Hak Atas Tanah di Indonesia - Suharyono Suharyono; Khalisah Hayatuddin; Muhamad Sadi Is (Jurnal HAM, 2022)
All living things philosophically need the land, especially humans. Human need land to maintain their lives. Based on it, the protection of human rights in obtaining land rights is essential as well as in defending their land rights. Defending the land means preserving life. The research problem in this paper is how the legal protection of human rights in obtaining land rights in Indonesia? This paper aims to learn about legal protection for human rights in obtaining land rights in Indonesia. Therefore, to maintain and ensure legal protection of human rights in obtaining land rights in Indonesia, it has been regulated in the 1945 Constitution of the Republic of Indonesia and then regulated explicitly in Law Number 5 of 1960 concerning Regulations about Basic Agrarian Fundamentals. However, it still has weaknesses in the legal protection of human rights in obtaining land rights in Indonesia. So, it can be concluded that the legal protection of human rights in obtaining land rights in Indonesia still has weaknesses. Therefore, the government and the DPR RI are supposed to immediately revise Law Number 5 of 1960 about Basic Regulations on Agrarian Principles.